Unraveling the Mott-Peierls intrigue in vanadium dioxide - Grandi, Francesco; Amaricci, Adriano; Fabrizio, M. (Physical Review Research, 2020)
Vanadium dioxide is one of the most studied strongly correlated materials. Nonetheless, the intertwining between electronic correlation and lattice effects has precluded a comprehensive description of the rutile metal to monoclinic insulator transition, in turn triggering a longstanding "the chicken or the egg" debate about which comes first, the Mott localization or the Peierls distortion. Here, we suggest that this problem is in fact ill posed: The electronic correlations and the lattice vibrations conspire to stabilize the monoclinic insulator, and so they must be both considered to not miss relevant pieces of the VO2 physics. Specifically, we design a minimal model for VO2 that includes all the important physical ingredients: the electronic correlations, the multiorbital character, and the two components of the antiferrodistortive mode that condense in the monoclinic insulator. We solve this model by dynamical mean-field theory within the adiabatic Born-Oppenheimer approximation. Consistently with the first-order character of the metal-insulator transition, the Born-Oppenheimer potential has a rich landscape, with minima corresponding to the undistorted phase and to the four equivalent distorted ones, and which translates into an equally rich thermodynamics that we uncover by the Monte Carlo method. Remarkably, we find that a distorted metal phase intrudes between the low-temperature distorted insulator and high-temperature undistorted metal, which sheds new light on the debated experimental evidence of a monoclinic metallic phase.
CRIS-Team WoS Importer:2021-01-22